1988
DOI: 10.1161/01.cir.77.5.1116
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of energy transfer from pressure-volume area to external mechanical work increases with contractile state and decreases with afterload in the left ventricle of the anesthetized closed-chest dog.

Abstract: We studied the effects of ventricular end-systolic elastance (Ees) and effective arterial elastance (Ea) on the efficiency of energy transfer from pressure-volume area (PVA) to external mechanical work (EW) in the left ventricle of anesthetized closed-chest dogs. PVA represents the total mechanical energy generated by ventricular contraction, which is an intermediate form of energy between oxygen consumption, the total energy input, and EW, the effective energy output. PVA and EW were determined from ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(64 citation statements)
references
References 23 publications
2
62
0
Order By: Relevance
“…Evaluation of left ventricular systolic performance in the PV plane during load alterations has given investigators a more specific tool to assess contractility in the in situ heart, because there appears to be less load dependency of such PV relationships than there is using single-beat preejection or ejection phase indices of performance (14,18,19). The conductance catheter has been used in the adult dog and human simultaneously with micromanometer pressure measurements for the repeated and instantaneous display and acquisition of PV loops without affecting ventricular function (13,26,29,36,43). PV loops have been analyzed by a variety of techniques (13,14,35,(44)(45)(46), but most commonly by generating ESPVR, to assess ventricular function in control conditions and in response to various hemodynamic perturbations.…”
Section: Parallel Conductance Versus Esv and Edvmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of left ventricular systolic performance in the PV plane during load alterations has given investigators a more specific tool to assess contractility in the in situ heart, because there appears to be less load dependency of such PV relationships than there is using single-beat preejection or ejection phase indices of performance (14,18,19). The conductance catheter has been used in the adult dog and human simultaneously with micromanometer pressure measurements for the repeated and instantaneous display and acquisition of PV loops without affecting ventricular function (13,26,29,36,43). PV loops have been analyzed by a variety of techniques (13,14,35,(44)(45)(46), but most commonly by generating ESPVR, to assess ventricular function in control conditions and in response to various hemodynamic perturbations.…”
Section: Parallel Conductance Versus Esv and Edvmentioning
confidence: 99%
“…In the adult, it has been extensively validated in situ in the dog and human (31)(32)(33) and in the isolated dog heart (34), and has been used to construct the ESPVR in both species (13,14,26,29,35,36). In the newborn, we have recently validated the catheter in the piglet against biplane cineangiography (37).…”
mentioning
confidence: 99%
“…So far, mechanical energy transfer using the PVA concept has been examined only under unphysiological states such as excised hearts or anesthetized animal models. [6][7][8][9] In the present study, we have extended the analysis of efficiency of energy transfer6'8 for the first time to human left ventricles. To clarify the insensitivity of mechanical efficiency to cardiac deterioration, we have examined, in patients with normal and moderately depressed hearts, how the changes in contractile state and afterload influence the MVo2-PVA relation and mechanical efficiency.…”
mentioning
confidence: 96%
“…LV-arterial coupling, which regulates SV at a given preload (51) and closely relates to LV mechanical efficiency (43), is a key determinant of optimal cardiovascular function. Previously, we demonstrated that normal-functioning LV and arterial system are nearly optimally coupled to produce SW both at rest and during exercise.…”
Section: Reversal Of the Adverse Effects Of Tachycardia On Lvarterialmentioning
confidence: 99%